On Weakly Semi-I-Open Sets and Another Decomposition of Continuity via Ideals - Hatir, Esref; Jafari, Saeid (Sarajevo Journal of Mathematics, 2024)
In this paper, we introduce the notions of weakly semi-I-open set and weakly semi-I-continuous functions to obtain a decomposition of continuity. We also investigated the fundamental properties of such functions. 1991 Mathematics Subject Classification. Primary: 54C10, 54A05; Secondary: 54D25, 54D30